(untitled) - Sene, Kevin (Berlin (Germany), 2008)
This book provides a comprehensive account of the flood forecasting, warning and emergency response process, including techniques for predicting the development of flood events, and for issuing appropriate warnings. Related topics, such as telemetry and information systems, and flood warning economics, are also discussed. For perhaps the first time, this book brings together in a single volume the many strands of this interesting multidisciplinary topic, and will serve as a reference for researchers, policy makers and engineers. The material on meteorological, hydrological and coastal modelling and monitoring may also be of interest to a wider audience.
Keywords: Flood forecasting,Natural disaster warning systems,Emergency management